Inactivation of bacterial biofilms using visible-light-activated unmodified ZnO nanorods. (8th August 2017) - Aponiene, Kristina; Serevičius, Tomas; Luksiene, Zivile; Juršėnas, Saulius
Abstract: Various zinc oxide (ZnO) nanostructures are widely used for photocatalytic antibacterial applications. Since ZnO possesses a wide bandgap, it is believed that only UV light may efficiently assist bacterial inactivation, and diverse crystal lattice modifications should be applied in order to narrow the bandgap for efficient visible-light absorption. In this work we show that even unmodified ZnO nanorods grown by an aqueous chemical growth technique are found to possess intrinsic defects that can be activated by visible light ( λ = 405 nm) and successfully applied for total inactivation of various highly resistant bacterial biofilms rather than more sensitive planktonic bacteria. Time-resolved fluorescence analysis has revealed that visible-light excitation creates long-lived charge carriers ( τ > 1 μ s), which might be crucial for destructive biochemical reactions achieving significant bacterial biofilm inactivation. ZnO nanorods covered with bacterial biofilms of Enterococcus faecalis MSCL 302 after illumination by visible light ( λ = 405 nm) were inactivated by 2 log, and Listeria monocytogenes ATCL3 C 7644 and Escherichia coli O157:H7 biofilms by 4 log. Heterogenic waste-water microbial biofilms, consisting of a mixed population of mesophilic bacteria after illumination with visible light were also completely destroyed.